Potential Role of Copper in Diabetes and Diabetic Kidney Disease - Guido Gembillo; Vincenzo Labbozzetta; Alfio Edoardo Giuffrida; Luigi Peritore; Vincenzo Calabrese; Claudia Spinella; Maria Rita Stancanelli; Eugenia Spallino; Luca Visconti; Domenico Santoro (Metabolites, 2022)
Copper is a fundamental element for the homeostasis of the body. It is the third most abundant essential transition metal in humans. Changes in the concentration of copper in the blood are responsible for numerous diseases affecting various organs, including the heart, brain, kidneys, and liver. Even small copper deficiencies can lead to the development and progression of several pathologies. On the other hand, excessive exposure to copper can cause toxicity in many human organs, leading to various systemic alterations. In the kidney, increased copper concentration in the blood can cause deposition of this element in the kidneys, leading to nephrotoxicity. One of the most interesting aspects of copper balance is its influence on diabetes and the progression of its complications, such as Diabetic Kidney Disease (DKD). Several studies have shown a close relationship between copper serum levels and altered glycemic control. An imbalance of copper can lead to the progression of diabetes-related complications and impaired antioxidant homeostasis. A high Zinc/Copper (Zn/Cu) ratio is associated with improved renal function and reduced risk of poor glycemic control in patients with type two diabetes mellitus (T2DM). Furthermore, the progression of DKD appears to be related to the extent of urinary copper excretion, while regulation of adequate serum copper concentration appears to prevent and treat DKD. The aim of this review is to evaluate the possible role of copper in DKD patients.